The use of green infrastructure elements in urban planning: environmental and economic efficiency (Международный научный журнал «Инженер», 2026)
This article presents an in-depth examination of the ecological and economic efficiency of green infrastructurecomponents within the context of modern urban planning. It explores the environmental and social benefits ofgreen spaces, vertical gardens, ecological transport systems, solar panels, and other energy-efficienttechnologies. Drawing on academic research, international case studies, and contemporary urban projects, thepaper analyzes how these elements contribute to the sustainability and livability of urban environments.Particular attention is given to current initiatives in Uzbekistan, such as the nationwide “Yashil Makon” (GreenSpace) campaign and the “New Andijon” smart city development. The study identifies key challenges includingregulatory barriers, limited technical capacity, and financial constraints. Based on these findings, the articleproposes practical recommendations aimed at improving the implementation and effectiveness of greeninfrastructure. This research contributes to the development of sustainable, resilient cities and highlights thestrategic role of environmental design in shaping healthier urban futures.